2000
DOI: 10.1002/1097-4636(200011)52:2<395::aid-jbm21>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

The cytotoxicity of corrosion products of nitinol stent wire on cultured smooth muscle cells

Abstract: Although nitinol is one of most popular materials of intravascular stents, there are still few confirmative biocompatibility data available, especially in vascular smooth muscle cells. In this report, the nitinol wires were corroded in Dulbecco's modified Eagle's medium with constant electrochemical breakdown voltage and the supernatant and precipitates of corrosion products were prepared as culture media. The dose and time effects of different concentrations of corrosion products on the growth and morphology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
82
0
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 183 publications
(89 citation statements)
references
References 23 publications
1
82
0
4
Order By: Relevance
“…In addition, their mechanical behavior is closer to the one of cortical bones, compared to usual biocompatible materials such as stainless steels and Ti-based alloys currently used. Ni-Ti family of alloys (also known through its Nitinol representative) has been the unique mark of the SMAs, and in spite of concerns related to the presence of Ni [1], the use in biological applications has been tolerated for some years due to the above mentioned complex of properties. In fact, the TiO 2 layer that is present at the surface of commercially finished material is thought to contribute to the good biocompatibility of Ni-Ti by acting as a barrier to Ni ion migration and dissolution out from the surface [2].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, their mechanical behavior is closer to the one of cortical bones, compared to usual biocompatible materials such as stainless steels and Ti-based alloys currently used. Ni-Ti family of alloys (also known through its Nitinol representative) has been the unique mark of the SMAs, and in spite of concerns related to the presence of Ni [1], the use in biological applications has been tolerated for some years due to the above mentioned complex of properties. In fact, the TiO 2 layer that is present at the surface of commercially finished material is thought to contribute to the good biocompatibility of Ni-Ti by acting as a barrier to Ni ion migration and dissolution out from the surface [2].…”
Section: Introductionmentioning
confidence: 99%
“…Além disso, possui grande elasticidade e resistência à fratura. Nitinol é a sigla de Nickel Titanium Naval Ordinance Laboratories, cuja liga metálica foi inicialmente desenvolvida para fins militares 18 A fratura de stents de nitinol pode estar relacionada ao polimento e ao revestimento da superfície do stent com óxidos amorfos 19,20 .…”
Section: Introductionunclassified
“…A liberação lenta de íons metais nos tecidos que circundam o local de implante do stent pode ser a razão da resposta inflamatória e hiperplásica local. Os produtos corrosivos das ligas de metal, comumente utilizados na fabricação de stents, (aço inoxidável 316 L e o nitinol) demonstram biotoxicidade 19,31 . O nitinol demonstrou ter efeito inflamatório por causar um aumento da secreção de interleucina-1 ß pelos monóci-tos 32 .…”
Section: Introductionunclassified
See 1 more Smart Citation
“…6,7 In a recent study, we demonstrated the cytotoxicity of corrosion products of nitinol stent wire on cultured smooth muscle cells. 8 In the present investigation, we aimed to study the effects of corrosion products of 316 L stainless steel wire on the growth and morphology of cultured rat aortic smooth muscle cells. In addition, the affected phases of cell replication were analyzed by cell cycle sorter.…”
Section: Introductionmentioning
confidence: 99%